THE EFFECT OF GCG IMPLEMENTATION AND RISK PROFILE ON FINANCIAL PERFORMANCE AT GO-PUBLIC NATIONAL COMMERCIAL BANKS - Sri Haryati; Emanuel Kristijadi (Journal of Indonesian Economy and Business (JIEB), 2014)
The research tests the effect of the risk profile and the application of corporate governance on financial performance at go-public national commercial bank. The data were taken from their financial statement and GCG assessment published during 2008-2010, analyzed using SEM with generalized structured component analysis (GSCA). It shows that risk profile has no significant and positive effect on the financial performance. Among the four risk profiles, liquidity risk has the best discriminate validity. However, GCG has significant and positive effect on the financial performance, and only financial and non financial transparency has the best convergent validity. Bank's five financial performance indicators have good validity. Beside, ROA, NIM and CAR have good validity in which ROA has the highest loading estimate.